Acute Kidney Injury Followed by Paraquat Poisoning With Relative Absence of Pulmonary and Renal Complaints : Story of a Survivor - Saha, Mrinal; Arjumand, Merina; Sattar, MA; Paul, Sujat (Journal of Chittagong Medical College Teachers’ Association, 2018)
A 16 years old girl admitted in the hospital after paraquat ingestion. She had oral ulceration and difficulty in swallowing. All her vital signs were normal including clear both lung fields. After few days, her tongue found coatedwith whitish debris. Her chest X-ray was normal but creatinine was 7.45 mg/dL despite normal urine output. After 2 cycle ofhemo dialysis her creatinine became normal. She had 2 unit of blood transfusion.After 3 weeks of hospital treatments she wasdischarged from hospital with all normal routine investigations including High Resolution Computed Tomography (HRCT) of both lungs. After one month of home stay she was alright on her last follow up. JCMCTA 2018 ; 29 (1) : 75-77